THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF JOB STRESS AND ROSTER WORK SYSTEMS ON ORGANIZATIONAL COMMITMENT OF ROSTER WORKERS IN MOROWALI - Rahmi Hermawati; Amelia Maharani Putri; Susi Adiawaty (Institut Bisnis Nusantara, 2025)
This study aims to analyze the influence of Job Stress and Roster Work Systems on Organizational Commitment, with Job Satisfaction acting as an intervening variable. This study is motivated by indications of low organizational commitment and high job stress among roster workers in Morowali. The research method used was quantitative and associative. The sample consisted of 150 roster workers in Morowali, using a non-probability sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results of the hypothesis test demonstrated that Job Stress and Roster Work Systems each significantly influence Job Satisfaction and Organizational Commitment. Furthermore, Job Satisfaction was shown to significantly influence Organizational Commitment. This study concludes that Job Satisfaction is an effective variable in mediating the influence of Job Stress and Roster Work Systems on Organizational Commitment.